MAGNETIC INDUCTION TOMOGRAPHY : GENERAL VIEW, CONCEPT AND APPLICATION - Ruzairi Abdul Rahim, 1967-, author; Zulkarnay Zakaria, 1976-, author; Muhammad Saiful Badri Mansor, 1986-, author; Jamaliah Idris, editor (Johor Bahru, Johor : Penerbit UTM Press, 2017)
Includes bibliographical references and index